Performance of a Matrix-Assisted Laser Desorption/Ionization Time-of-Flight Mass Spectrometry Testing Algorithm for the Rapid Identification of Clinical Filamentous Molds - Fissel, John A.; Holdren-Serrell, Carrie K.; Memon, Warda; Zhang, Sean X. (Frontiers in Cellular and Infection Microbiology, 2022)
One of the most significant challenges in the treatment of fungal infections is the relatively long turnaround time (TAT) required for fungal species identification. The length of TAT to identification can impact patient clinical outcomes by delaying appropriate targeted therapy. Matrix-Assisted Laser Desorption/Ionization Time-of-Flight Mass Spectrometry (MALDI-TOF MS) has demonstrated exceptional utility in the rapid identification of bacteria and yeasts in the clinical microbiology laboratory. The capability of MALDI-TOF MS for rapid identification of clinical isolates presents an opportunity for significant advancement in the identification of filamentous molds. In this study, we employed a diagnostic algorithm using MALDI-TOF MS for the rapid identification of filamentous molds in order to assess the impact of this technology on TATs. The majority of isolates included in this study were able to be identified by MALDI-TOF MS (78%). Further, these isolates were identified in less than three days from first detection of colony growth. This study demonstrates the utility of MALDI-TOF MS in the rapid identification of filamentous molds in the clinical mycology laboratory.